Understanding critical variables contributing to competitive advantages of international high-speed railway contractors - Niu, Yanliang; Deng, Xiaopeng; Zhang, Limao; Duan, Xiaochen (Journal of Civil Engineering and Management, 2019)
This article is devoted to identifying and explaining the critical variables contributing to competitive advantages in international High-Speed Railway (HSR) projects from the contractor’s perspective. A total of 24 variables were identified by the literature review and a pilot study. An international questionnaire survey was performed to obtain professional opinions from both practitioners and the academy. The 24 variables were ranked and clustered into 6 factors using exploratory factor analysis. Furthermore, a case study of the Early Train Operator project of the California HSR was carried out by the survey, interview, and first-hand data. The results indicated that the top six ranked variables are (1) None Accident History, (2) Eligibility & International Criteria, (3) Contract Reputation, (4) Marketing Strategy, (5) Risk Management Capability, and (6) Technical Responsiveness. Furthermore, the 24 variables are grouped into six dimensions: Glocalization, Marketing, Safety, Economics, Technology, and Responsibility. The case study indicated that the factor framework was suitable and tractable for the application. The findings of this paper could (1) assist international HSR contractors in obtaining a better understanding of the deeper determinates of competitive advantages and (2) serve as a valuable reference for developing their competitive advantages in the international HSR market.